Pengenalan Pengenalan Huruf Dari Tepung Sebagai Stimulasi Literasi Pada Anak Usia Dini Di TK Prawidia Mambal Badung - Suryawan, I Gde; Ida Bagus Komang Sindu Putra (PRATAMA WIDYA : Jurnal Pendidikan Anak Usia Dini, 2026)
Early literacy is an important foundation in the development of language skills and academic readiness in early childhood. One of the main aspects of early literacy is the ability to recognize letters of the alphabet, which needs to be stimulated through activities that are appropriate to the characteristics of children's development. This study aimed to describe the use of flour as a learning medium in introducing letters of the alphabet and its impact on stimulating early literacy in children at Prawidia Kumara Mambal Kindergarten. This study used a descriptive qualitative approach with 10 children in group B and 2 class teachers as research subjects. Data collection techniques included participatory observation of children's activities during learning activities, semi-structured interviews with teachers to determine perceptions, benefits, and obstacles in implementing activities, and documentation in the form of photographs, children's work, and field notes. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results showed that the use of flour as a medium for introducing letters was able to increase children's interest in learning, active involvement, and concentration, as well as support fine motor development and the ability to recognize letter shapes. Children showed high enthusiasm, courage to try, and an increase in the number of letters recognized. Thus, the use of flour as a material can be an alternative medium for early literacy learning that is innovative, affordable, and appropriate to the characteristics of young children.